PEMANFAATAN TEKNIK AKROSTIK UNTUK MENINGKATKAN KEMAMPUAN MENULIS PUISI SISWA KELAS VIII SMP - Nurul Khairani Abduh (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
Abstract. The Utilization of Acrostic Technique to Increase Student Writing Poetry Skill of Class VIII SMP. This study aims to describe the process and the results of learning to write poetry students by using acrostic techniques. This type of research is a classroom action research consisting of two cycles. Data analysis technique is done descriptively quantitative and qualitative. The subjects of this study are teachers and students of class VIII SMP Negeri 22 Makassar. Based on result of the study found that (1) the mastery of learning shows a quality improvement of 14.8 percent and (2) the result of student writing poetry showed an increase from the average value of 75 in cycle one to 80 in cycle two. Based on these results, acrostic technique is recommended for learning to write poetry in JHS.